The Greatest Spiritual Wealth of the Language - Ergashovna, Saidova Gavhar; Nilufar Zakir, Bekimbetova (International Journal of Formal Education, 2025)
Every nation has its own history and, of course, its own native language. Therefore, we, young people, should also respect our native language and be able to use it correctly in various situations. In this article, you will learn about our language, as well as what we need to do to preserve it, and learn about the contribution of our ancestors to our language.